High‐performance 110 kVp hard x‐ray detector based on all‐crystalline‐surface passivated perovskite single crystals - Juyoung Ko; Beomjun Park; Jangwon Byun; Sandeep Pandey; Ajin Jo; Joo‐Hong Lee; Wonho Lee; Jin‐Wook Lee; Nam‐Gyu Park; Man‐Jong Lee (InfoMat, 2024)
Abstract Halide perovskite single crystals (SCs) have attracted much attention for their application in high‐performance x‐ray detectors owing to their desirable properties, including low defect density, high mobility–lifetime product (μτ), and long carrier diffusion length. However, suppressing the inherent defects in perovskites and overcoming the ion migration primarily caused by these defects remains a challenge. This study proposes a facile process for dipping Cs0.05FA0.9MA0.05PbI3 SCs synthesized by a solution‐based inverse temperature crystallization method into a 2‐phenylethylammonium iodide (PEAI) solution to reduce the number of defects, inhibit ion migration, and increase x‐ray sensitivity. Compared to conventional spin coating, this simple dipping process forms a two‐dimensional PEA2PbI4 layer on all SC surfaces without further treatment, effectively passivating all surfaces of the inherently defective SCs and minimizing ion migration. As a result, the PEAI‐treated perovskite SC‐based x‐ray detector achieves a record x‐ray sensitivity of 1.3 × 105 μC Gyair−1 cm−2 with a bias voltage of 30 V at realistic clinical dose rates of 1–5 mGy s−1 (peak potential of 110 kVp), which is 6 times more sensitive than an untreated SC‐based detector and 3 orders of magnitude more sensitive than a commercial α‐Se‐based detector. Furthermore, the PEAI‐treated‐perovskite SC‐based x‐ray detector exhibits a low detection limit (73 nGy s−1), improved x‐ray response, and clear x‐ray images by a scanning method, highlighting the effectiveness of the PEAI dipping approach for fabricating next‐generation x‐ray detectors.